The impact of diabetes on employment in Mexico - Till Seuring; Yevgeniy Goryakin; Marc Suhrcke (University of East Anglia, Health Economics Group (HEG), 2014)
This study explores the impact of diabetes on employment in Mexico using data from the Mexican Family Life Survey (MxFLS) (2005), taking into account the possible endogeneity of diabetes via an instrumental variable estimation strategy. We find that diabetes significantly decreases employment probabilities for men by about 9.9 percent (p<0.01) and somewhat less so for women - 4.2 percent (p<0.1) - without any indication of diabetes being endogenous. Further analysis shows that diabetes mainly affects the employment probabilities of people above the age of 44 and also has stronger effects on the poor than on the rich, particularly for men. Our results highlight -for the first time - the detrimental employment impact of diabetes in a developing country.
Keywords: I10; J01; 330; diabetes; employment; instrumental variables; Mexico